Measuring Impairments of Mentalization with the 15-Item Mentalization Questionnaire (MZQ) and Introducing the MZQ-6 Short Scale: Reliability, Validity and Norm Values Based on a Representative Sample of the German Population - David Riedl; Hanna Kampling; Tobias Nolte; Astrid Lampe; Manfred E. Beutel; Elmar Brähler; Johannes Kruse (Diagnostics, 2022)
Deficits in mentalization are indicated by impaired emotional awareness and self-reflectiveness, and are associated with various mental disorders. However, there is a lack of validated research instruments. In this study, the psychometric properties of the Mentalization Questionnaire (MZQ) were evaluated in a representative German population sample with n = 2487 participants. Analyses included evaluation of the MZQs acceptance, reliability, and validity. Factorial validity was established with exploratory (EFA) and confirmatory factor analyses (CFA) after the dataset was randomly split. Dimensionality was evaluated with a bi-factor model. For convergent validity, correlations with the OPD SQS, PHQ-4, and POMS were calculated. While acceptance was good, internal consistencies (ω = 0.65–0.79) and factor structure of the original four subscales were not acceptable (TLI = 0.87, CFI = 0.91, RMSEA = 0.071). EFA indicated a 3-factor solution, which was not confirmed by CFA (TLI = 0.89, CFI = 0.91, RMSEA = 0.073). Correlations between subscales and bi-factor analyses indicated an underlying general factor (TLI = 0.94, CFI = 0.96, RMSEA = 0.053). A shortened 6-item version was comparable to the original scale. Age and sex-specific representative norm-values are presented. The MZQ is a feasible, reliable and valid self-report instrument to measure representations of inner mental states. However, when applied to non-clinical samples, the total score of the MZQ should be used.